2022
DOI: 10.15252/emmm.202012435
|View full text |Cite
|
Sign up to set email alerts
|

Biological foundations of successful bacteriophage therapy

Abstract: Bacteriophages (phages) are selective viral predators of bacteria. Abundant and ubiquitous in nature, phages can be used to treat bacterial infections (phage therapy), including refractory infections and those resistant to antibiotics. However, despite an abundance of anecdotal evidence of efficacy, significant hurdles remain before routine implementation of phage therapy into medical practice, including a dearth of robust clinical trial data. Phage-bacterium interactions are complex and diverse, characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 318 publications
0
29
0
Order By: Relevance
“…The first phage activity dated back to 1896, when Ernest Hankin reported that the waters from the rivers Ganges and Yamuna in India possessed antibacterial activity against Vibrio cholerae [ 69 ]. In the late 1910s, and following initial work by the English bacteriologists Ernest Hankin and Frederick Twort, a French microbiologist from the Pasteur Institute (Felix d’Herelle, 1917) identified viruses that specifically and selectively parasitized bacteria and named them “bacterium eaters” (bacteriophages) [ 70 , 71 ]. It was d’Herelle who first developed the notion of using phages therapeutically to treat bacterial infection with encouraging results [ 69 ].…”
Section: Phage Therapeuticsmentioning
confidence: 99%
“…The first phage activity dated back to 1896, when Ernest Hankin reported that the waters from the rivers Ganges and Yamuna in India possessed antibacterial activity against Vibrio cholerae [ 69 ]. In the late 1910s, and following initial work by the English bacteriologists Ernest Hankin and Frederick Twort, a French microbiologist from the Pasteur Institute (Felix d’Herelle, 1917) identified viruses that specifically and selectively parasitized bacteria and named them “bacterium eaters” (bacteriophages) [ 70 , 71 ]. It was d’Herelle who first developed the notion of using phages therapeutically to treat bacterial infection with encouraging results [ 69 ].…”
Section: Phage Therapeuticsmentioning
confidence: 99%
“…One possible means of reducing unwanted bacteria is to use taxa specific phages to reduce their numbers. Phage therapy is being used in medicine to treat human pathogens (Pirnay et al, 2022;Venturini et al, 2022) and more recently to control plant pathogens (Ye et al, 2019). Unfortunately, the bacteria associated here with Asiatic bittersweet can be beneficial to other plants in this ecosystem therefore it may not be reasonable to eliminate them.…”
Section: Phylummentioning
confidence: 99%
“…[ 14 ] Similar strategies include bacteriophage therapy, in which bacterial viruses are used to infect drug‐resistant bacteria and induce lysis, [ 15 ] but although it has been reported that the introduction of living microorganisms can have an excellent antibacterial effect, controllability and biosafety still need to be considered. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…[14] Similar strategies include bacteriophage therapy, in which bacterial viruses are used to infect drug-resistant bacteria and induce lysis, [15] but although it has been reported that the introduction of living microorganisms can have an excellent antibacterial effect, controllability and biosafety still need to be considered. [16] To our knowledge, combining the advantages of probiotics and NO to design a safe and efficient method of infected wound healing has rarely been discussed, and no practical way to simultaneously avoid all the potential problems in treating infected wounds has been reported. Therefore, a facile and broadly applicable strategy is necessary to realize the combination of low-risk probiotics and low-dosage NO for antibacterial treatment.…”
Section: Introductionmentioning
confidence: 99%